Monitoring internal and external load during volleyball competition - Gielen, J.; Mehuys, E.; Berckmans, D.; Meeusen, R.; Aerts, J. M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The aim of this study was to identify the relationships between continuously measured internal and external load variables during volleyball competition.